How to publish in international (Indexed) journals - Quayum, Mohammad Abdul (2018)
Discuss the ways to successfully publish in reputable international journals. Why it is important and how it contributes to our academic career. What are the do's and don't's in the process and how to identify the right journal for publishing an article.